Transfer of Appropriate Technology from Malaysian Cooperatives to Indonesia: A Perspective of Mechanical Engineering in Service - Indrayani, Tri Irfa; Salfadri Salfadri; Yohanis; Zufiayu Sapiun (Journal of Community Service and Application of Science, 2025)
International Community Service (PKM) has carried out activities in cross-border collaboration, especially between cooperatives in Malaysia and Indonesia. Mock study activities and field visits to leading cooperatives such as ANGKASA Malaysia which stands for ANGKASA is (Angkatan Koperasi Kebangsaan Malaysia Berhad), This cooperative is the Malaysian national peak cooperative that oversees all types of cooperatives, functioning as a representative body of the Malaysian cooperative movement. Known for its very large membership scale (12 million+), focusing on the socioeconomic well-being of members, facilitating payroll deduction loans. and the service team digitally transformed with an updated credit and service ecosystem to face the modern era, becoming an example of a large cooperative that is actively developing the potential of cooperatives in Malaysia. The adoption of appropriate technology plays a significant role in the efficiency and productivity of cooperative business units. Through a mechanical engineering perspective, this team examines the potential for technology transfer that can be adapted by higher education cooperatives in Indonesia, including agricultural product processing systems, mechanization of production businesses, and automation of cooperative data management. The results of the study show that the simple but effective application of engineering techniques, such as the use of semi-automatic packaging machines and digital inventory systems, is able to increase the efficiency of cooperative work by up to 30%. These findings provide important recommendations for cross-border technology transfer strategies within the framework of cooperative-based economic strengthening. This article contributes to the development of transnational cooperative partnership models and the relevance of engineering in community economic empowerment through cooperatives.